Pre-cultivation with Selected Prebiotics Enhances the Survival and the Stress Response of Lactobacillus rhamnosus Strains in Simulated Gastrointestinal Transit - Succi, Mariantonietta; Tremonte, Patrizio; Pannella, Gianfranco; Tipaldi, Luca; Cozzolino, Autilia; Romaniello, Rossana; Sorrentino, Elena; Coppola, Raffaele (Frontiers in Microbiology, 2017)
In our study, we dwelled upon combinations of lactobacilli/prebiotics, considering four different strains belonging to the Lb. rhamnosus species, including LGG, and different prebiotics often found in commercial synbiotic products, such as inulin, lactulose and polyols mannitol and sorbitol. In the first step of the research, the survival, the growth kinetic parameters and the protein expression of Lb. rhamnosus strains cultivated in presence of the different prebiotics as a unique carbon source were evaluated. In the second step, the influence of pre-cultivation in medium added of metabolizable prebiotics on the strains survival to simulated gastrointestinal (GI) transit, assayed without prebiotics addition, was estimated. Our results showed that the presence in the medium of certain low fermented prebiotics, specific for each strain, represents a stress factor that significantly affects the growth of Lb. rhamnosus strains, inducing the up-regulation of several proteins. In detail, all added prebiotics used as unique carbon source caused a growth retard compared with glucose, as testified by increased values of the lag phase and decreased values of the µmax. Mannitol evidenced intermediate µmax values between those registered with glucose and those detected with the other assayed prebiotics. Moreover, the cultivation with prebiotics induced the over expression of 7 protein bands. Interestingly, we found a correlation between the up-regulation of two specific stress proteins, called P4 (ATP-binding subunit Clpx) and P7 (GrpE), and the death kinetic parameters (resistance and cells viability) registered during the simulated GI transit of strains pre-cultivated with specific, low fermented prebiotics. Specifically, the highest resistance and gastric-vitality scores were highlighted for the strain AT195 when pre-cultivated in presence of sorbitol. Conversely, the lowest values were found in the case of DSM20021 pre-cultivated with mannitol. Among the up-regulated stress proteins, P7 resulted involved in the response to the starvation. Finally, it is possible to conclude that the pre-cultivation with certain prebiotics as a unique carbon source represents a strain-specific, sub-lethal stress able to enhance the resistance of Lb. rhamnosus strains and consequently their viability under simulated GI transit.